A novel gelcasting of alumina suspension using curdlan gelation. Issue 9 (November 2015) - Xu, Jie; Zhang, Yanxue; Gan, Ke; Zhang, Xiaoyan; Qu, Yanan; Ma, Ning; Yang, Jinlong
Abstract: A novel nontoxic system for gelcasting of alumina suspensions was investigated using curdlan as gelling agent. The rheological and gelling behavior of curdlan suspensions in the temperature range 10–85 °C either on heating or cooling were studied. Influences of concentration of curdlan and solid loading of alumina suspension on the rheological properties and gelling behavior of alumina suspension were investigated. Complex shaped green bodies with compressive strength around 3.7 MPa were obtained by heating 50 vol% alumina suspensions with 0.625–0.750 wt% curdlan (based on alumina powder) at 80 °C for 1 h and by subsequently cooling to room temperature. Dense alumina parts with relative density above 98% have been prepared by curdlan gelation with homogeneous microstructures and good mechanical properties.